Komparasi model guided discovery dan model guided inquiry: Pengaruhnya terhadap kemampuan berpikir analitis siswa SMA - Anggun Faradila Sandi; Hadi Soekamto; Syamsul Bachri; Yuswanti Ariani Wirahayu (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
One of the Importance of analytical thinking skills is needed on 21st-century learning and is a higher order thinking ability required in the 20133 curriculum. So this ability is needed in geography learning to prepare students to face everyday life's challenges. Efforts to influence it can be done through guided discovery learning and guided inquiry learning. The two models require students to actively participate in learning activities in order to acquire analytical thinking skills. This research aims to compare which of the two models is superior for developing analytical thinking skills. Researchers use quasy experiments with design post-test only control group. The research subjects are 11 IPS 1 as experimental class 1 and 11 IPS 2 as experimental class 2. The research sites in SMAN 8 Malang. The students’ analytical thinking skills were measured using 11 essay questions that were valid and reliable. The data analysis using independent sample t-test. The t-test result shows significance 0,034 less than equal to 0,05 so that H0 was rejected, H1 was received. That matter concluded that there is a difference in analytical thinking skills of experimental student one and experimental student two. The result also shows the guided inquiry model is superior to the guided discovery model. The reason is that there is a syntax to formulate a hypothesis on the guided inquiry model so that affects students’ analytical thinking skills. Pentingnya kemampuan berpikir analitis salah satunya dibutuhkan pada pembelajaran abad 21 dan merupakan kemampuan tingkat tinggi yang diperlukan pada kurikulum geografi 2013. Sehingga kemampuan ini dibutuhkan dalam pembelajaran geografi untuk mempersiapkan siswa menghadapi tantangan kehidupan sehari-hari. Upaya dalam mempengaruhinya dapat dilakukan melalui model guided discovery dan model guided inquiry. Kedua model tersebut menuntut siswa untuk berpartisipasi aktif pada kegiatan pembelajaran guna memperoleh kemampuan berpikir analitis. Tujuan studi ini adalah mengkomparasikan kedua model tersebut mana yang lebih unggul untuk mengembangkan kemampuan berpikir analitis siswa. Peneliti menggunakan Quasy Experiment dengan Design Posttest Only Control Group. Subjek penelitian adalah siswa kelas 11 IPS 1 sebagai kelas eksperimen 1 dan 11 IPS 2 sebagai kelas eksperimen 2, adapun lokasi penelitian di SMAN 8 Malang. Kemampuan berpikir analitis siswa diukur dengan 11 soal esai yang telah valid serta reliabel. Analisis Data menggunakan uji independent sample t-test. hasil uji t-test menujukkan signifikansi 0,034 kurang dari sama dengan 0,05 sehingga H0 ditolak, H1 diterima. Hal tersebut disimpulkan bahwa terdapat perbedaan kemampuan berpikir analitis siswa eksperimen 1 dan siswa Eksperimen 2. Hasil juga menjukkan model guided inquiry lebih unggul dibandingkan model guided discovery. Penyebabnya adalah terdapat sintak merumuskan hipotesis pada model guided inquiry sehingga lebih mempengaruhi kemampuan berpikir analitis siswa.